Enhanced HIV-1 surveillance using molecular epidemiology to study and monitor HIV-1 outbreaks among intravenous drug users (IDUs) in Athens and Bucharest. - Paraskevis, Dimitrios; Paraschiv, Simona; Sypsa, Vana; Nikolopoulos, Georgios; Tsiara, Chryssa; Magiorkinis, Gkikas; Psichogiou, Mina; Flampouris, Andreas; Mardarescu, Mariana; Niculescu, Iulia; Batan, Ionelia; Malliori, Meni; et al. (Infect Genet Evol, 2015)
BACKGROUND: A significant increase in HIV-1 diagnoses was reported among Injecting Drug Users (IDUs) in the Athens (17-fold) and Bucharest (9-fold) metropolitan areas starting 2011. METHODS: Molecular analyses were conducted on HIV-1 sequences from IDUs comprising 51% and 20% of the diagnosed cases among IDUs during 2011-2013 for Greece and Romania, respectively. Phylodynamic analyses were performed using the newly developed birth-death serial skyline model which allows estimating of important epidemiological parameters, as implemented in BEAST programme. RESULTS: Most infections (>90%) occurred within four and three IDU local transmission networks in Athens and Bucharest, respectively. For all Romanian clusters, the viral strains originated from local circulating strains, whereas in Athens, the local strains seeded only two of the four sub-outbreaks. Birth-death skyline plots suggest a more explosive nature for sub-outbreaks in Bucharest than in Athens. In Athens, two sub-outbreaks had been controlled (Re<1.0) by 2013 and two appeared to be endemic (Re∼1). In Bucharest one outbreak continued to expand (Re>1.0) and two had been controlled (Re<1.0). The lead times were shorter for the outbreak in Athens than in Bucharest. CONCLUSIONS: Enhanced molecular surveillance proved useful to gain information about the origin, causal pathways, dispersal patterns and transmission dynamics of the outbreaks that can be useful in a public health setting.
Keywords: Disease Outbreaks; Greece; HIV Infections; HIV-1; Humans; molecular epidemiology; Phylogeny; Phylogeography; Public Health Surveillance; RNA, Viral; Romania; Substance Abuse, Intravenous